Fibula graft for reconstruction by defect of removal of mandibular ameloblastoma multicystic - Fajardo, Williams (2019)
A case of mandibular bone tumor, diagnosed as multicystic ameloblastoma, which was surgically managed, and is presented in the following article. This type of pathology is of odontogenic origin and in spite of being benign it has an aggressive behavior and usually requires a radical approach. After evaluating the case, the surgical removal of the tumor was chosen, which included wide mandibular bone recession with safety margins of 1cm followed by an immediate reconstruction with a fibula free flap. Surgical treatment was performed in the Dos de Mayo National Hospital’s, operating room, in charge of the Head and Neck and Maxillofacial Surgery Service, with a favorable evolution and without complications, waiting for oral rehabilitation